PENINGKATAN AKTIFITAS DAN PRESTASI BELAJAR SISWA SMA MATEMATIKA MATERI LIMIT MELALUI MODEL TUTOR TEMAN SEBAYA (TTS) VARIASI - Eni Rosetti (Pedagonal : Jurnal Ilmiah Pendidikan, 2020)
IMPROVEMENT OF LEARNING ACTIVITIES AND ACHIEVEMENTS OF SENIOR HIGH SCHOOL STUDENTS ON LESSONS OF LIMIT THROUGH VARIATION PEER-TEACHING MODELSThis research aims to improve Mathematics learning activities and improve mathematics learning achievement of the Limit material through the variation peer-teaching models model for class XI MIPA 3 students in the 2018/2019 academic year. This research was conducted at SMA Negeri 9 Bogor. This research was conducted from January 2019 to June 2019. The subjects in this Classroom Action Research were students of SMA Negeri 9 Bogor in class XI MIPA 3, totaling 35 students consisting of 13 male students and 22 female students. Data collection techniques with written tests and observations. Data analysis using comparative description analysis and qualitative description. The results of this Classroom Action Research are: students' mathematics learning activities in the initial conditions, cycle I and cycle II have increased. The average score of student learning activities in the initial conditions of 2.74 increased to 3.77 in the first cycle and increased to 4.30 in the second cycle, while the mathematics learning achievement of students in the initial conditions, cycle I and cycle II increased. The average value of student achievement in the initial conditions of 39.13 increased to 71.17 in the first cycle and increased to 88.13 in the second cycle. The percentage of students who completed also increased, in the initial condition, students who completed learning were only 17.14%, increasing to 50% in cycle I and increasing to 80% in cycle II. This increase is due to the variation peer-teaching models learning method, all students can be actively involved in learning. Students who are appointed as tutors are active in helping their group members overcome learning difficulties. Students who have difficulty learning actively ask questions and discuss with tutors who are their own friends.